2022
DOI: 10.1111/jgh.15939
|View full text |Cite
|
Sign up to set email alerts
|

7‐day versus 14‐day tegoprazan‐based triple therapy to treat Helicobacter pylori infection: Real‐world evidence

Abstract: Background and Aim: Potassium-competitive acid blockers (P-CABs) can be used to eradicate Helicobacter pylori infection. We aimed to evaluate the impact of treatment duration (7 vs 14 days) on successful H. pylori eradication with P-CAB-based triple therapy in Korea, where clarithromycin resistance rate is high. Methods: We retrospectively reviewed the data of patients who received first-line treatment for H. pylori infection with tegoprazan-based triple therapy (50 mg tegoprazan + 1000 mg amoxicillin + 500 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…[27][28][29][30] Likewise, previous studies investigating tegoprazan-based TT regimens have shown most AEs to be mild, requiring no medical management, with the most frequent ones being gastrointestinal disorders. [31][32][33][34] Our study found a 23.4% rate of AEs associated with tegoprazan-based TT, consistent with prior studies. Owing to the lack of relevant medical records, AE rates for lansoprazole-based TT could not be determined.…”
Section: Discussionsupporting
confidence: 89%
“…[27][28][29][30] Likewise, previous studies investigating tegoprazan-based TT regimens have shown most AEs to be mild, requiring no medical management, with the most frequent ones being gastrointestinal disorders. [31][32][33][34] Our study found a 23.4% rate of AEs associated with tegoprazan-based TT, consistent with prior studies. Owing to the lack of relevant medical records, AE rates for lansoprazole-based TT could not be determined.…”
Section: Discussionsupporting
confidence: 89%
“…Drug adherence was defined as the administration of ≥80% of prescribed medications. The severity of adverse events was assessed as mild (transient symptoms that improved spontaneously), moderate (symptoms that required management), or severe (symptoms that led to emergency visits) ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Southern Italy is a geographical region where the clarithromycin resistance rate exceeds 20% [6]. For this reason, triple therapy effectiveness has decreased and, therefore, cannot be recommended any more [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%